TEACHING BLIND CHILDREN TO PLAY MUSIC (Academicia Globe: Inderscience Research, 2023)
In this article, there are ideas about creating special manuals for the acquisition of musical knowledge by blind young people, and it was proved that they have a high level of musical performance, just like healthy children.